Triple-negative breast cancer: unmet needs and emerging targeted and immunotherapeutic approaches - Diya Agarwal; Ammana Sathwika Reddy; Balasani Ashwitha; Muppasani Thanvitha; Mamidala Ravalika (International Journal of Basic & Clinical Pharmacology, 2026)
Triple-negative breast cancer (TNBC) is a tough type of breast cancer. It does not have estrogen, progesterone, or HER2 receptors. This makes it hard to treat because common hormone and HER2 therapies do not work, often leading to poor results. To look at new treatments for TNBC, focusing on new molecular targets, antibody-drug conjugates (ADCs), immunotherapy, resistance issues, and future personalized medicine. A detailed review was done, combining information from molecular biology, clinical trials, immuno-oncology, and new technologies like artificial intelligence and liquid biopsy to assess progress in TNBC treatment. TNBC is very diverse at the molecular level, involving pathways like PI3K/AKT, TP53 mutations, and DNA repair problems. New treatments include ADCs like sacituzumab govitecan targeting TROP-2, and immune checkpoint inhibitors targeting PD-1/PD-L1 pathways, which have helped some patients live longer. Combining ADCs and immunotherapy shows better results by causing cancer cells to die in a way that triggers the immune system. However, resistance to treatment is still a big problem due to tumor diversity, loss of antigens, poor drug delivery, and resistance to the drug's effects. Advances in liquid biopsy, ctDNA monitoring, and AI-driven models are helping create real-time, personalized treatment plans. TNBC treatment is moving from standard chemotherapy to more precise approaches using targeted therapies, immunotherapy, and flexible treatment plans. Despite progress, overcoming resistance and improving long-term survival need more research into biomarkers, combination therapies, and personalized medicine.